2009
DOI: 10.1103/physrevb.80.224408
|View full text |Cite
|
Sign up to set email alerts
|

Multiple magnetic ordering phenomena evaluated by heat capacity measurements inEr1xTbxAl2Laves-phase al

Abstract: Heat capacity measurements in zero and applied magnetic fields have been performed on a series of Er 1−x Tb x Al 2 pseudobinary Laves-phase alloys. Different anomalies that change with Tb concentrations have been observed. These anomalies represent multiple magnetic ordering phenomena, similar to those reported in Er 1−x Pr x and Er 1−x Dy x Al 2 alloys. In common, all alloys contain mixtures of lanthanide metals with opposite signs of the second-order Steven's operators, which were believed to cause competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
(30 reference statements)
3
16
0
Order By: Relevance
“…11,12 The 4f charge density of Er 3+ is a prolate spheroid, whereas the 4f charge densities of The lattice parameter for pure TmAl 2 (7.7757 Å) was taken from the report of Harris et al 21 As shown in the inset of Fig. 1, the lattice parameters depend linearly on the Tb concentration (x).…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 The 4f charge density of Er 3+ is a prolate spheroid, whereas the 4f charge densities of The lattice parameter for pure TmAl 2 (7.7757 Å) was taken from the report of Harris et al 21 As shown in the inset of Fig. 1, the lattice parameters depend linearly on the Tb concentration (x).…”
Section: +mentioning
confidence: 99%
“…It was proposed that the observed behavior is a result of the competition between the magnetoelastic and quadrupolar effects, which is caused by the modification of the magnetic structure due to Dy and Tb doping. 10,11,12 It was also suggested that the modification of the magnetic structure of the Er 1-x Dy x Al 2 and Er 1-x Tb x Al 2 systems was mainly caused by the 4f charge densities of Er 3+ being different from Dy 3+ and Tb…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recent studies showed that when two lanthanides with 4f electron charge densities of different shape are mixed together in pseudo-binary R 1-x R' x Al 2 compounds (R and R' are lanthanide metals where R has a positive second order Stevens' factor and the same for R' is negative ), interesting magnetic phenomena are observed. 3,4,5,6,7 For certain critical concentrations centered at x = 0.25, sharp peaks, representing first order phase transitions, are observed in the heat capacity, C P , data of the R 1-x R' x Al 2 alloys. The peaks are suppressed upon the application of weak magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Multiple magnetic ordering transitions were recently discovered in pseudo-binary R 1-x R' x Al 2 alloys, where R and R' are rare earth metals with second order Steven's factors of opposite sign. 27,28,29,30 Hence, mixing of two lanthanide metals can result in unusual behaviors not only in pseudo-binary lanthanide metals but also in rare earth based intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%